Pertimbangan Hukum Hakim Terhadap Anak Kekerasan Fisik Dalam Rumah Tangga (Putusan Nomor: 326/Pid.Sus/2019/PN.Amb) - Regina Latuheru; Margie Gladies Sopacua; Astuti Nur Fadillah (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Children who experience criminal acts of physical violence are very vulnerable to mental and psychological shocks. Legal assistance and protection of children who are victims of criminal acts is the duty and responsibility of parents and the surrounding environment, but in some cases parents commit violence against the children themselves so that they must accept the consequences in the form of imprisonment in accordance with the judge's decision through his consideration. The purpose of this research is intended to obtain clarity and legal certainty by identifying and analyzing